Effect of Yellow Pumpkin (Cucurbita moschata) Flour Addition on Proximate Levels and Calories of White Millet (Panicum miliaceum) Flakes - Hazna Zhavira; N Nurwantoro; Heni Rizqiati (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
This research aims to determine the effect of adding pumpkin flour with different concentrations to the proximate levels and calories of white millet flakes. Complete randomized design used in this research with 4 treatments and 5 replications. This research consisted of formulations which was divided into 4 treatments in the form of adding pumpkin flour with concentrations of 0%, 10%, 20%, and 30% w/w white millet. The material used was white millet, pumpkin, sugar, salt, and water. Proximate levels were calculated using proximate analysis while calories was calculated based on the calculation of carbohydrate, protein, and fat composition of the samples produced. The results showed that the addition of pumpkin flour with different concentrations had a significant effect (p<0.05) on protein content, fat content, ash content, crude fiber content, carbohydrate content, calories, and had no effect (p>0.05) on water content. As conclusion, the addition of pumpkin flour 30% was the best treatment proved by its highest fiber content and low in calories.